Penanaman Nilai Toleransi dan Empati Sejak Dini Melalui Bimbingan Sosial Teknik Circle Time di Sekolah Dasar: kajian Systematic Literature Review - Faizin, Muhammad (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
This study is motivated by the increasing issues of intolerance and the decline in social sensitivity among elementary school children, which have implications for the weakening of empathy and cooperation skills within the learning environment. The study aims to identify the effectiveness of applying social guidance through the Circle Time technique in elementary school, fostering tolerance and empathy from an early age. The research employs a Systematic Literature Review (SLR) using the PRISMA approach, encompassing the identification, screening, eligibility, and inclusion of ten relevant articles published between 2015 and 2024 concerning children’s social-emotional education, Circle Time, and character learning in elementary education. The analysis results indicate that Circle Time is highly effective in enhancing positive student interactions, fostering active listening skills, promoting respect for differences, and strengthening children's emotional and social awareness. The findings also reveal that the success of this technique largely depends on teachers’ competence in managing group dynamics and creating a safe and inclusive classroom environment. The discussion emphasizes that social guidance based on the Circle Time approach serves not only as a pedagogical strategy but also as a preventive intervention against discriminatory behavior and student conflicts. Implicatively, the study recommends integrating the Circle Time program into the elementary school counseling curriculum to shape students' adaptive, tolerant, and empathetic social and emotional character in today's multicultural era.